Choosing simplicity : a commentary on the Bhikshuni Pratimoksha - Yin, Wu.; Jendy; Thubten Chodron (Ithaca, N.Y. : Snow Lion Publications, 2001)
Choosing Simplicity discusses the precepts and lifestyle of fully ordained nuns within the Buddhist tradition. The ordination vows act as guidelines to promote harmony both within the individual and within the community by regulating and thereby simplifying one's relationships to other sangha members and laypeople, as well as to the needs of daily life. Observing these precepts and practicing the Buddhadharma brings incredible benefit to oneself and others. Since the nuns' precepts include those for monks and have additional rules for nuns, this book is useful for anyone interested in monastic life. As a record of women's struggle not only to achieve a life of self-discipline, but also to create harmonious independent religious communities of women, Choosing Simplicity is a pioneering work.
Includes bibliographical references (p. [333]-338).
Keywords: Buddhist monasticism and religious orders for women -- Rules